2021
DOI: 10.1016/j.ebr.2021.100499
|View full text |Cite
|
Sign up to set email alerts
|

Functional neurological disorder: Engaging patients in treatment

Abstract: Patients with a functional neurological disorder can be difficult to engage in treatment. The reasons for this are complex and may be related to physician, patient and health care system issues. Providers contribute to difficulties in treatment engagement by giving confusing explanations for the patient symptoms, stigmatizing patients, and not allowing patients time to voice their questions and concerns. Patient factors include a lack of engagement after an explanation of the diagnosis, resistance to treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Additionally, it was shown that some aspects of the holistic approach in treating FNDs could be applied in PPCS with promising results [91][92][93], and this could be a reason to suspect that they are based on similar grounds in terms of symptoms persistence mechanisms, or that the holistic approach is generally of use in multiple component neurological disorders. However, some studies reported that the provider-patient relationship could be affected by an FND diagnosis [62,94,95]; thus, further research could better describe the degree of overlap between FND and PPCS in order to find the source of similarity between them or to test the possibility that the mechanistical aspects could better suggest overlaps with other chronic neurological disorders.…”
Section: Critiques and Limitations Of The Fnd Model For Ppcsmentioning
confidence: 99%
“…Additionally, it was shown that some aspects of the holistic approach in treating FNDs could be applied in PPCS with promising results [91][92][93], and this could be a reason to suspect that they are based on similar grounds in terms of symptoms persistence mechanisms, or that the holistic approach is generally of use in multiple component neurological disorders. However, some studies reported that the provider-patient relationship could be affected by an FND diagnosis [62,94,95]; thus, further research could better describe the degree of overlap between FND and PPCS in order to find the source of similarity between them or to test the possibility that the mechanistical aspects could better suggest overlaps with other chronic neurological disorders.…”
Section: Critiques and Limitations Of The Fnd Model For Ppcsmentioning
confidence: 99%
“…Similarly, lack of engagement after a proper explanation of the diagnosis, resistance to treatment, and family and work dynamics along with prior negative experiences with the health care system are several patient-related factors that affect outcomes. 198 Several issues that further contribute to poor treatment adherence include communication gaps, and patient, provider, and system barriers, which must be carefully addressed. 199,200 Notwithstanding, it is essential to remember that a diagnosis of FND does not rule out the possibility of another comorbid neurological disorder; in fact, a co-existent neurological disorder is itself a risk factor for FND and it is important to note the possibility of other concurrent or future medical comorbidities like comorbid epilepsy or PD.…”
Section: Etiological Basis and Pathophysiologymentioning
confidence: 99%
“…Coordinating explanations among multiple clinicians, especially with those who the patient already trusts, can prove to be quite helpful, as poor adherence negatively impacts the outcomes. Similarly, lack of engagement after a proper explanation of the diagnosis, resistance to treatment, and family and work dynamics along with prior negative experiences with the health care system are several patient-related factors that affect outcomes 198. Several issues that further contribute to poor treatment adherence include communication gaps, and patient, provider, and system barriers, which must be carefully addressed 199,200.…”
Section: Managementmentioning
confidence: 99%
“…In Australia, individuals with FS struggle to access specialised treatment 22. Barriers to treatment include a lack of knowledge of functional disorders among health professionals, referral patterns, circular healthcare pathways, with patients often falling between the cracks of different medical specialties in public versus private healthcare and between physical and mental healthcare 15 23 24. Limited access to specialised treatment services for FS catalysed our research team to develop R e -PROGRAM, an internet-based therapy for FS.…”
Section: Introductionmentioning
confidence: 99%